Consensus on core competencies for simulation training in ultrasound-guided renal biopsy - Andrea J. Doyle; Colin P. Cantwell; Claire Mulhall; Richard Arnett; Claire M. Condron (PLoS ONE, 2025)
Rationale and objectives To define the competencies in ultrasound knowledge and skills that are essential for interventional radiology trainees to master when performing ultrasound-guided renal biopsy, and to design simulation-based training to develop these competencies. Materials and methods A whole-task training and competency-based assessment methodology was adopted. 42 fellowship-trained interventional radiologists were contacted to participate in the process. An anonymous three-round modified Delphi process was used to identify and assess the crucial procedural steps in performing an ultrasound-guided renal procedure. The primary survey round allowed free text submission of the procedure steps. The primary survey was analysed to identify the common key tasks and these were grouped in procedural domains. For rounds two and three consensus on key steps was evaluated. 75% agreement was required to progress to the final task list. The final task list was reviewed to identify simulation strategies. Results Nine interventional radiologists completed the three-round modified Delphi process. 24 competencies were determined to be important across the seven procedural domains. One competency identifying contraindications was removed due to disagreement among participants. The educational review of the final task list identified simulation strategies: three domains involving simulated participants and four domains requiring hybrid simulation involving simulated participants, simulator training and interprofessional simulation. Conclusion Twenty-three competencies were identified in a blueprint for the development of a simulation curriculum to meet the training requirement of radiologists performing ultrasound-guided renal biopsy.